Assessment of the New Regional Plan in Mongolia with regards to Rural Development and Urbanization Issues based on Arkhangai and Uvurkhangai Provinces - Otgonbayar , Munkhbayasgalan; Zsigmond, Major (Economica, 2024)
This study discusses the relationship between the rural development process in Mongolia regards to its rapid urbanization issues.This paper took Arkhangai and Uvurkhangai, two similar provinces, and compared their rural development from 2013 to 2021 to understand the complex relationship between rural development and urbanization issues. A chain-based method, fixed-based method as well as per capita methods were used to get more accurate results from the comparison. The results confirmed that ongoing rural-to-urban migration due to more access of education, workplace, etc. (due to its more attractive factors) slows down the development of such factors in that rural area, putting the whole process in a cycle. As for the two provinces, the infrastructure, education, health level is all similar, but their potential economic growth is specialized in two different sectors. Arkhangai has more agricultural products due to its land and soil resources and Uvurkhangai has more potential for the tourism sector. It can be concluded that the government’s new plan of dividing the country into six regions with specialized enterprises would be a good idea for future rural development projects (previously there were only four regions existing).